y=-3x^2+18x-25 move constant to other side
y+25=-3x^2+18x make leading coefficient 1 by dividing every thing by -3
(y+25)/-3=x^2-6x halve the linear coefficient, square it, add it to both sides...ie (-6/2)^2=9, so add 9 to both sides
(y+25-27)/-3=x^2-6x+9 now the right side is a perfect square
(y-2)/-3=(x-3)^2 now multiply both sides by -3
y-2=-3(x-3)^2 add 2 to both sides
y=-3(x-3)^2+2
f(x)=-3(x-3)^2+2
So the vertex here is an absolute maximum for the parabola as anything squared and then multiplied by a negative will decrease the value of y.
So the absolute maximum for f(x) occurs at the vertex (3, 2)